Szombathely mezőváros hitelezési gyakorlata 1850 és 1860 között = The landing practice of the market town of szombathely between 1850 and 1860 - Halász, Imre (Közép-Európai Közlemények, 2018)
Credit has always been needed. After the development of the financial institution system in the capitalism the landing practice is obvious for all: everyone who needs loan for business or individual life-style turns to savings banks or banks. The lecture and the study intend to describe the practice of landing before the financial institutions became widely present based on the practice of the diocesan market town Szombathely. The capital investments of the orphans’ funds are well-known, furthermore we can read about much smaller volume investments of some church funds. This lecture shows the financial management system of the seat of Vas county, therefore it investigates the investment and interest charging practice of some funds suggested by the reference. It aims to describe the operation of one town fund as a model, and reviews the borrowers’ most important economic and social features.